(untitled) (International conference on multidisciplinary science, 2023)
It is known that the implementation of advanced pedagogy and new information technologies in education not only increases the effectiveness of training sessions, but also in the education of an independent and logically thinking, well-rounded and highly moral person by applying the achievements of science in practice. is important.